Successfully contesting the policy sphere: examining through the press a case of local protests changing new ecological laws - Castro, P.; Seixas, E.; Neca, P.; Bettencourt, L. (Political Psychology, 2018)
It is crucial to gain better insights into how psychosocial processes can limit the power of the political/legislative sphere for promoting social change through new laws. One form of accomplishing this is by illuminating the arguments and the content and value of social representations at play in cases in which the public sphere succeeds in contesting new laws. In this article, we explore a case of successful resistance to new ecological laws in a Portuguese Natura site. The laws, restricting recreational fishing, were made less stringent after meeting with local opposition. Content analysis of 122 articles published from 2006 to 2014 in regional and national newspapers reveals that protestors (fishermen, local authorities) received higher visibility and support and had more direct voice than the political sphere in both presses. Dialogical analysis of direct quotations of protestors shows how they seek legitimacy by establishing common ground with valued representations, vividly invoking people-place bonds and tradition, and also how they attempt to undermine the law's legitimacy by linking local and national concerns, avoiding (potentially devalued) “Nimby” (“not in my backyard”) arguments. The discussion highlights what can be learned from using the press to investigate policy struggles that successfully organized their argumentation to contest new laws.